Conflict Analysis in Stromberg’s Movie “Maleficent” - Surya Adi Saputra, I Kadek (Humanis, 2018)
The title of this paper is Conflict Analysis in Stromberg’s Movie “Maleficent”. It is aimed at finding out kinds of conflict faced by the main character and the sources of the main character’s conflict and analyzing the way the main characters solve the conflict.  The data of this study were taken from a movie entitled “ Maleficent” . This study focuses on describing external and internal conflicts. The conflict is analyzed based on the theory of conflict proposed by Kenney (1966) who divides conflicts into two types, external and internal conflicts. The description of the presentation of the characters is analyzed based on the theory proposed by Deetz & Stevenson (1986) who divides it into two; they are the source of conflict and resolution of conflict. The result of this study shows that the main character faces two conflicts; external and internal conflicts. The sources of the main character are incompatible goals, and different opinions. In managing the conflict, the main character uses avoidance strategy, competition strategy and creative integration.